1998
DOI: 10.1111/j.1467-842x.1998.tb01419.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of gender and socio-economic status on dietary patterns and nutrient intakes in 18-year-old Australians

Abstract: A therosclerosis has its origins in childhood and tracking of risk factors for cardiovascular disease from childhood to adult life is re~ognised.'-~ Adoption of healthy behaviours early in life has been encouraged with the aim of reducing later risk of cardiovascular d i~e a s e .~ In childhood, dietary behaviour is largely influenced by family eating patterns but, during adolescence, changes in health-related behaviour and attitudes affect dietary choices in young Diet-related behaviour in young adults is lik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
54
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(59 citation statements)
references
References 32 publications
4
54
1
Order By: Relevance
“…As in the sample of British adolescents 13 , significant gender differences were found in our study sample, indicated by a lower overall intake of PRAL in girls and partly gender-specific age trends of food intake. Such 'healthier' food choices and preferences in girls were also reported for different age groups in several other studies [15][16][17][18] .…”
Section: Discussionsupporting
confidence: 77%
“…As in the sample of British adolescents 13 , significant gender differences were found in our study sample, indicated by a lower overall intake of PRAL in girls and partly gender-specific age trends of food intake. Such 'healthier' food choices and preferences in girls were also reported for different age groups in several other studies [15][16][17][18] .…”
Section: Discussionsupporting
confidence: 77%
“…For example, in previous studies of the Australian population those of lower SES have been shown to consume a greater proportion of their energy as refined sugars (Baghurst et al, 1989), and have a diet higher in fat density (Baghurst et al, 1990;Milligan, et al, 1998;Smith & Owen, 1992;Webb et al, 1999), lower in fibre density (Baghurst et al, 1990;Smith & Owen, 1992;Webb et al, 1999), and lower in density of intake for a range of micronutrients (Baghurst et al, 1990;Milligan et al, 1998;Webb et al, 1999). Socioeconomic differentials in intakes have been observed in other developed countries including the USA (Shimakawa et al, 1994;Wynn, 1987), Sweden (Wallstrom et al, 2000;Wamala et al, 1999), the UK (Bartley et al, 2000;Thompson et al, 1993), and elsewhere in Europe (Irala-Estevez et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies showed their widespread use in children (Northstone and Emmett, 2005;Alexy et al, 2008;Pryer and Rogers, 2009), adolescents (Milligan et al, 1998) and adults (Pryer et al, 2001;Johnson-Down et al, 2006) in western countries.…”
Section: Introductionmentioning
confidence: 99%
“…Dietary surveys that examine the association between CF and food intake or nutrient intake are scare, but pointed to unfavourable dietary habits (Milligan et al, 1998;Pryer et al, 2001;Pryer and Rogers, 2009). In addition, the energy dense (ED), which refers to the amount of energy in a given weight of food (kJ per gram), of typical CF products, such as pizza, is high.…”
Section: Introductionmentioning
confidence: 99%